Engineering Design Process Engineering Student Centered Experience Learning (ESCEL) di Jurusan Teknik Elektro Universitas Maritim Raja Ali Haji (UMRAH) - Nusyirwan, Deny (Fakultas Teknik Universitas Maritim Raja Ali Haji, 2017)
Department of Electrical Engineering of Universitas Maritim Raja Ali Haji (FT UMRAH) has seen the importance of providing an understanding of Engineering Design Process (EDP) for engineering students through the learning process of Student Centered Experience Learning (ESCEL), the need to improve the creativity and innovation of students in all lectures and projects, therefore the electrical engineering majors have also started to develop the existing syllabus to be able to encourage the creation of science behind great product design and no less important as majors that have prioritized internationalization as prepare technopreunership course as a basic model that will be applied the experience learning, and in the future will be planned for the international credit transfer course at one of the universities in Europe.